2012
DOI: 10.1073/pnas.1109243109
|View full text |Cite|
|
Sign up to set email alerts
|

Structure-property relationships of a biological mesocrystal in the adult sea urchin spine

Abstract: Structuring over many length scales is a design strategy widely used in Nature to create materials with unique functional properties. We here present a comprehensive analysis of an adult sea urchin spine, and in revealing a complex, hierarchical structure, show how Nature fabricates a material which diffracts as a single crystal of calcite and yet fractures as a glassy material. Each spine comprises a highly oriented array of Mg-calcite nanocrystals in which amorphous regions and macromolecules are embedded. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
366
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(386 citation statements)
references
References 50 publications
16
366
1
3
Order By: Relevance
“…There is a gradient in porosity, with porosity increasing substantially from~10% on the surface and in the growth rings to~60% in the medullary core. These spines are a model for biologically controlled crystal growth and consist of a mesocrystal [164,165]. Originally Fig.…”
Section: Sea Urchin Spinesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a gradient in porosity, with porosity increasing substantially from~10% on the surface and in the growth rings to~60% in the medullary core. These spines are a model for biologically controlled crystal growth and consist of a mesocrystal [164,165]. Originally Fig.…”
Section: Sea Urchin Spinesmentioning
confidence: 99%
“…thought to be a single crystal [166,167], it has recently been shown that the structure consists of periodic and uniform nanocrystals, 30-50 nm in diameter, with parallel crystallographic alignment (Fig. 22a-b) [68,[163][164][165]. These nanocrystals are held together with layers of amino acids (mainly aspartic and glutamic acid) with a thickness of several hundred nanometers [165][166][167].…”
Section: Sea Urchin Spinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] These bioinspired methods are characterized by mild reaction conditions and promise the ability to generate structures comparable to those found in nature. Central to biogenic control over mineralization is the use of soluble organic additives, where these can even guide the assembly of composite materials [4][5][6][7][8][9] with superior mechanical properties. [ 3,4,10 ] Many bioinspired mineralization strategies therefore utilize either naturally extracted biomacromolecules or their synthetic analogues, [ 1,2,5,7,9,10 ] and even small organic species such as amino acids and surfactants can exert considerable control over mineralization, sometimes supporting the formation of complex particle assemblies.…”
Section: Doi: 101002/adma201403185mentioning
confidence: 99%
“…Central to biogenic control over mineralization is the use of soluble organic additives, where these can even guide the assembly of composite materials [4][5][6][7][8][9] with superior mechanical properties. [ 3,4,10 ] Many bioinspired mineralization strategies therefore utilize either naturally extracted biomacromolecules or their synthetic analogues, [ 1,2,5,7,9,10 ] and even small organic species such as amino acids and surfactants can exert considerable control over mineralization, sometimes supporting the formation of complex particle assemblies. [ 5,6,8,[11][12][13] While attractive, however, this approach is still hampered by the diffi culty in selecting appropriate organic additives-and in particular combinations of additives-to give materials with target structures and properties.…”
mentioning
confidence: 99%